Comparison of the Friedewald formula with the precipitate method for the determination of LDL cholesterol levels in cattle - Osorio, José Henry (2018)
The aim of this study was to compare two methods (precipitate and Friedewald) for the determination of LDL cholesterol values in cattle. Blood samples were taken from 56 cattle in early morning. In the serum LDL cholesterol levels were determined by the precipitation method and the Friedewald formula. The results were analyzed using a oneway analysis of variance. The precipitated method reported values (mg/dl) of 14.33, 0.36, 59.11, 58.75 and 11.21 for average, minimum, maximum, range and standard deviation, respectively, and by the Friedewald method values (mg/dl) were 62.04, 13.68, 156.82, 143.14 and 32.97 respectively, with significant difference between the two methods for a confidence level of 95.0%. The results indicate that the use of the precipitation method for the determination of LDL cholesterol in cattle is not recommended.